Functional efficiency of cell-engineered liver constructs based on tissue-specific matrix (experimental model of chronic liver failure) - M. Yu. Shagidulin; N. A. Onishchenko; Yu. B. Basok; A. M. Grigoriev; A. D. Kirillova; E. A. Nemets; E. A. Volkova; I. M. Iljinsky; N. P. Mozheiko; V. I. Sevastianov; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Objective: to investigate the functional efficiency of a cell-engineered construct (CEC) of the liver based on tissuespecific matrix consisting of decellularized rat liver fragments, allogeneic liver cells and multipotent mesenchymal stromal cells (MSCs) isolated from the bone marrow on an experimental model of chronic liver failure (CLF).Materials and methods. In creating liver CECs, the liver for decellularization and liver cells were obtained from male Wistar rats. MSCs were isolated from rat bone marrow. The functional efficacy of CEC was investigated on an experimental CLF model obtained by priming rats with CCl4 solution. At different periods after implantation, the outcomes were assessed based on the biochemical parameters of cytolysis.  Morphological changes in the liver were analyzed by histochemical methods in the control (administration of saline solution into the liver parenchyma) and experimental (administration of liver CEC into the liver parenchyma) groups. Results. It was shown that implantation of the proposed CEC normalizes blood biochemical parameters and structural disorders of the damaged rat liver faster (by day 30 after introduction of CEC instead of day 180 in the control). The CEC was also shown to have reduced animal mortality from 50 to 0%, which is due to early activation of proliferation of viable liver cells and faster formation of new blood vessels. These effects are down to either stimulation of the internal regenerative potential of the damaged liver during CEC implantation or long-term functioning of the transplanted cells as part of the CEC based on the decellularized liver matrix. Conclusion. The liver CEC, implanted into the liver parenchyma in laboratory animals with a CLF model, has a functional activity.